Rhenium-188 Labeled Hydroxyapatite and Rhenium-188 Sulfur Colloid - Grillenberger, K. G.; Glatz, S.; Reske, S. N. (Nuklearmedizin - NuclearMedicine, 1997)
Aim: One therapeutic approach to rheumatoid arthritis and other inflammatory arthropathies besides surgical removal of inflamed synovium is radiation synovectomy using beta-emitting radionuclides to destroy the affected synovial tissue. Up to now the major problem associated with the use of labeled particles or colloids has been considerable leakage of radionuclides from the injected joint coupled with high radiation doses to liver and other non target organs. In this study we compared 188Re labeled hydroxyapatite particles and 188Re rhenium sulfur colloid for their potential use in radiation synovectomy. Methods: To this end we varied the labeling conditions (concentrations, pH-value, heating procedure) and analyzed the labeling yield, radiochemical purity, and in vitro stability of the resulting radiopharmaceutical. Results: After optimizing labeling conditions we achieved a labeling yield of more than 80% for 188Re hydroxyapatite and more than 90% for the rhenium sulfur colloid. Both of the radiopharmaceuticals can be prepared under aseptic conditions using an autoclav for heating without loss of activity. In vitro stability studies using various challenge solutions (water, normal saline, diluted synovial fluid) showed that 188Re labeled hydroxyapatite particles lost about 80% of their activity within 5 d in synovial fluid. Rhenium sulfur colloid on the other hand proved to be very stable with a remaining activity of more than 93% after 5 d in diluted synovial fluid. Conclusion: These in vitro results suggest that 188Re labeled rhenium sulfur colloid expects to be more suitable for therapeutic use in radiation synovectomy than the labeled hydroxyapatite particles.
Keywords: Rhenium-188; radiation synovectomy; Hydroxyapatite; rheumatoid arthritis